POLLEN MORPHOLOGY OF CONTORTAE (ACANTHACEAE) - Scotland, R (1993)
Variation in pollen morphology is described and illustrated for 36 genera of Acanthaceae with contorted corolla aestivation. A parsimony analysis of pollen characters is presented. © 1993 The Linnean Society of London.